Academia journal of biology Volume 43, Number 2 (H. Vietnam academy of science and technology, 2021)
Contents: Isolation and identification of endophytic fungi from Catharanthus roseus and Scutallaria barbata; Association between genotypes of TLR4 gene rs2149356 polymorphism and serum level of IL-6 in Vietnamese patients with gout; Expression of gene coding endoglucanase GH5-4 derived from meagenomic DNA data of bacteria in goats rumen in Escherichia coli;...
Formerly Tạp chí sinh học (Journal of Biology)
Keywords: Sinh học; Tạp chí